Zakat fund in Malaysia: where does it all go? / Roshaiza Taha ... [et al.] - Taha, Roshaiza; Mohd Nor, Mohd Nazli; Embong, Mohd Rodzi; Zulkifli, Muhammad Faris (Accounting Research Institute (ARI), Universiti Teknologi MARA (UiTM), 2017)
The purpose of this paper is to investigate the management performance, especially the distribution performance of Zakat institutions in Malaysia. Although this study is carried out in Malaysia, Zakat issues are prevalent religious issues which affect Muslims all over the world and thus this study may offer some insights on Zakat management to interested parties. The secondary data is used where information on Zakat fund from Zakat institutions are analyzed to determine their performance. Document analysis is carried out on annual reports, published bulletins, brochures, and periodical news of Zakat institutions in the selected region to assess the performance of these institutions. The results suggest that Zakat institutions in their distribution practices have adhered to the stipulated Islamic law, whereby, Zakat fund is distributed to the eight qualified groups of recipients. The main contentious issue in Zakat is the existence of a large percentage of undistributed Zakat which does not appear in any Zakat reporting. This issue is very serious and needs to be addressed by the Muslim communities and this issue may also be present in other Muslim countries. This study provides the public and the stakeholders, first-hand information regarding the existing management issues of Zakat fund in Malaysia and thus, contributes to the sharing of Zakat management experience to other Muslim countries for a better solution.